Optimalizace a zavedení standardizovaných postupů ve výrobě přírub pro Common Rail vysokotlakých čerpadel. - Doležal, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Cílem projektu optimalizace a zavedení standardizovaných postupů ve výrobě přírub je na základě časových snímků a MTM analýz naplánovat popsat a zavést optimální postupy, určit standardy, vypracovat standardizované postupy u vícestrojové obsluhy, vizuální kontroly. Zaučit pracovníky podle nového postupu. Od projektu je očekávána stabilizace procesu, snížení rozpracované výroby, zvýšení kvality a objemu výroby přírub na 2200 ks za den pro jednu linku. Provést porovnání vlivu optimalizace na operace v procesu výroby příruby, u pracovišť vizuální kontroly kvantitativní posouzení různých pracovních postupů pomocí statistických metod (R&R Studie).

Objective of the Project of optimization and introduction of standardized procedures in flange production is to plan, determine and introduce optimal procedures based on time scan and MTM analysis; to determine standards, to establish standardized procedures for multi -machine operation and visual control and to train personnel according to new procedure. Project is expected to stabilize process, decrease work in process production, improve quality and increase volume of flange production to 2200 pieces per day for one production line. Furthermore to provide comparison of standardization influence on operations in flange production process, to perform quantitative analysis of several working instructions on visual control workplaces by statistics method (R&R study).
Optimization and use of standardized manufacturing routines for the Common Rail Flange production of high pressure pumps.
Keywords: MTM; Procesní analýza; Standardizace; MSA; MTM; Process Analysis; Standardized procedures; Standardization